Impacts of transfusion in β-thalassemia major patients receiving multiple blood transfusions - Singh, Virendra; Meena, Battilal; Bihari, Naseem A.; Sharma, Mahendra (International Journal of Research in Medical Sciences, 2018)
Background: Beta-thalassemia major is one of major public health problems in India. Thalassemia major is a transfusion-dependent severe anemia and these children experience various problems if the transfusion is inadequate but at the same time repeated blood transfusions are associated with hazards like iron overload. Methods: This study was conducted at thalassemia ward of S.M.S Hospital and J.K.LON paediatrics Hospital, Jaipur from April 2012 to Nov. 2013. 145 thalassemia patients on transfusion therapy attending outdoor or being admitted were assessed after obtaining due permission from the authorities and consent from the guardian or parents of patients. Results: Present study comprised 145 beta-thalassemia major patients with 51 (35%) females and 94 (65%) males in which youngest patient is 3 years old and the oldest 33 years. 104 (72%) were Hindus and 41 (28%) were Muslims. Consanguinity was found in a significant proportion 16% (23) of the parents of the patients. 137 (94%) patients had serum ferritin ³1000ng/ml. Out 145 thalassemic patients, 108 (74.5%) have total serum bilirubin >1(mg/dl), 103 (71%) have SGPT level >35IU, 103 (71%) have SGOT level >40IU), 38 (26.2%) have serum alkaline phosphatase level >390 IU, 35 (24.1%) have serum creatinine level >1.6mg/dl, 42 (29%) have serum urea level >45mg/dl, 28 (19.3%) have serum uric acid level >6mg/dl. Conclusions: It is suggested to revise and devise suitable transfusion regime so that a balance between adequate transfusion and minimum side effects of multiple transfusions is maintained. Systemic effects of multiple transfusions should be rigorously and meticulously studied.